Determinants of aortic bioprosthetic valve calcification assessed by multidetector CT. Issue 6 (24th January 2015) - Mahjoub, Haïfa; Mathieu, Patrick; Larose, Eric; Dahou, Abdelaziz; Sénéchal, Mario; Dumesnil, Jean-Gaston; Després, Jean-Pierre; Pibarot, Philippe
Abstract : Background: Cusp calcification is the main mechanism leading to bioprosthetic heart valve (BPV) failure. Recent studies suggest that BPV calcification is an active rather than passive process probably modulated by several mechanisms including lipid-mediated inflammation and dysfunctional phosphocalcic metabolism. Objective: To identify the clinical and metabolic determinants of BPV calcification assessed by multidetector CT (MDCT). Methods and results: Presence of BPV calcification was assessed by MDCT in 194 patients who had undergone aortic valve replacement. A calcification score was individually calculated and expressed in mm 3 . Patients also underwent a clinical evaluation, a Doppler echocardiographic exam, and a plasma lipid and phosphocalcic profile. 46 patients (24%) had BPV calcification (cusp calcification score >0 mm 3 ). After adjustment for age, gender, and time interval since BPV implantation, increased calcium–phosphorus product (OR 1.11, 95% CI 1.01 to 1.23 per 1 unit; p=0.02) and the presence of prosthesis-patient mismatch (OR 3.67, 95% CI 1.25 to 10.6; p=0.01) were the strongest independent factors associated with BPV calcification. Calcium supplement intake, age and female gender were independently associated with increased calcium–phosphorus product. Conclusions: This study suggests that higher calcium–phosphorus product and prosthesis–patient mismatch promote BPV calcification. Furthermore, this study reports that calcium supplements, which are extensively prescribed in elderly patients, are independently associated with higher calcium–phosphorus product.